(3GdehGbas - (3eMeO Hf YHO GdLHGQ Hf GdMSf GdfaQjs
(3ChdgG (B:s
(3ehba GdYR Chbafi ai GdYR hbGd di dGjSJbd Hg Ohfi TF hdG jUdM ef Ohfi TF CfG GdYR hGdPi dGjSJWGY eLGhQJg s
(3BNQgG (B:s
(3Chbafi hbGd di MLGHc cdeG CXgQJ hMLGHc cdeG CSQOJ gPG BNQ GdLRA GdPi hLO HNWg QVi Gddg Yfg hCQVGg s
(3jdi GdeNWhW YOI fbhds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI edi edc (B(4263) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs